RELATIONSHIP BETWEEN ANXIETY LEVELS WITH SLEEP QUALITY IN PRIMIGRAVIDA THIRD-TRIMESTER PREGNANCY AT JEUMPA MATERNITY HOSPITAL PONTIANAK - Michela Hengrawi Harianto; Wilson Wilson; Eka Ardiani Putri (JURNAL KEDOKTERAN DAN KESEHATAN, 2020)
Background Anxiety is an emotional condition characterized by tension, fear and anxiety, accompanied by somatic symptoms (headache, sweating, palpitation, chest tightness, and mild stomach upset), which is one of the psychological aspect affecting pregnancy, especially primigravida pregnancy. Anxiety stimulates the body to be difficult to relax in pregnant woman that can cause the decrease of sleep duration resulting in sleep disturbance. The objective of this study was to assess the relationship between anxiety levels with sleep quality in primigravida third-trimester pregnancy.Method Observational analytic research was used in this research with cross-sectional approach. A total of 43 people were involved in this research. Variable in this research were anxiety levels and sleep quality. Data were analyzed using Kolmogorov-Smirnov test with SPSS 23.Result The result showed there was significant relationship between anxiety levels with sleep quality among primigravida third-trimester pregnant women at Jeumpa Maternity Hospital Pontianak.Conclusion This study concludes that there is relationship between anxiety levels with sleep quality among primigravida third-trimester pregnant women at Jeumpa Maternity Hospital Pontianak.